ANALISIS FILM UPIN & IPIN DALAM PENANAMAN KARAKTER PEDULI SOSIAL - Dony Septyawan (FKIP, PGSD, Universitas Slamet Riyadi, 2018)
This research is motivated by the large number of television shows that contain negative content that is often watched by elementary school-age children and animated films upin and ipin which contain the value of social caring character for planting for children in grade III SDB 02 Karangbener. This study aims to determine the value of the character of social care in television shows Upin and Ipin season 5 episode